Sound Symbolism and Onomatopoeia: (with special reference to English, Armenian and Russian) - Khachatryan, Armine (Armenian Folia Anglistika, 2015)
The function, realization and the role of sound-symbolic phenomenon can vary in some languages. The study of sound symbolism and onomatopoeia in Armenian, Russian and English showed that highly expressive forms of language occur not only in daily conversation, advertising, newspapers and magazines, but also in creative literature: children’s poems, stories and great works of art. As a powerful stylistic device they realize an impact upon the reader or listener and evoke certain emotional expressively evaluative reactions. The comparative analysis of this phenomenon demonstrates that the word is heard differently in different cultures.
Keywords: onomatopoeia; sound symbolism; alliteration; assonance